President Biden’s foreign policy doctrine and advancing US assistance to Ukraine - Iryna Dudko; Vladyslav Faraponov (Американська історія і політика, 2023)
The purpose of this article is to analyze the United States’ support to Ukraine during the war with Russia, as well as in the months leading up to Russia’s full-scale invasion of Ukraine in February 2022. This issue remains relevant to conceptualizing US assistance to Ukraine to expel Russian forces from its territory. In particular, we claim that among other policy alternatives, the Biden administration deliberately chose to support Ukraine «for as long as it takes». Thus, we analyze the amount and comprehensiveness of support to Ukraine, which we consider to be in Washington’s core interests, as well as US efforts in terms of policy-making.